The obesity paradox: defining the impact of body mass index and diabetes mellitus for patients with non‐muscle‐invasive bladder cancer treated with bacillus Calmette–Guérin. (5th December 2020) - Brooks, Nathan A.; Kokorovic, Andrea; Xiao, Lianchen; Matulay, Justin T.; Li, Roger; Ranasinghe, Weranja K.B.; Nagaraju, Supriya; Shen, Yu; Gao, Jianjun; Navai, Neema; Dinney, Colin P.N.; Grossman, H. Barton; et al.
Abstract : Objectives: To evaluate if the obesity paradox, wherein obesity portends worse overall prognosis for a disease but improved outcomes for patients receiving immunotherapy, exists for patients receiving bacillus Calmette–Guérin (BCG) in a contemporary cohort. Patients and Methods: We performed an Institutional Review Board‐approved database review to identify patients with non‐muscle‐invasive bladder cancer (NMIBC) completing at least an induction course of BCG. Clinicopathological variables collected included: body mass index (BMI), medications, and diabetes mellitus (DM). Outcomes of interest included: recurrence‐free (RFS), progression‐free (PFS), cancer‐specific (CSS), and overall survival (OS). Univariate and multivariate modelling were used to evaluate the association between outcomes and clinical factors. Results: A total of 579 patients (median follow‐up 4.6 years) received BCG induction for NMIBC; 90% had high‐grade disease (47.2% clinical stage T1). In all, 75.7% of patients were overweight or obese and 18% had DM. Aspirin, statins, metformin and β‐blockers were used in 34%, 42%, 11%, and 29% of patients, respectively. Overweight and obese patients had improved PFS, CSS and OS. DM was associated with worse RFS. Medications of interest had no association with outcomes. Conclusion: Elevated BMI is associated with improved outcomes in patients with NMIBC treated with BCG immunotherapy. Patients with DM are at increased risk of recurrence. These findings support a potential obesity paradox in bladder cancer. Evaluation of the underlying mechanism and the role of global patient assessment, counselling, and risk factor modification are warranted.